Correlation and Path Coefficient Analysis of Seed Yield and Yield Components in Some Faba Bean Genotypes in Sulaimani Region - Tofiq, Sherwan E.; Aziz, Omer K.; Salih, Sazgar H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
The present study was conducted at Agricultural Research Center of Bakrajo, Sulaimani, Iraq during three successive seasons 2011-2014. This research was conducted using seven faba bean cultivars namely (Zaina, Seher, Yieldiz, Civilla, Luz di Otono, Tanyari and local). The following measurements and observations were made: 100 seed weight, first node height, number of seeds/plant, number of seeds/pod, pod length, number of pods/plant and seed yield. The results indicated that highly significant and negative correlations were presented between 100 seed weight and seed yield, whereas, significant and positive correlations were presented between the numbers of seed/plant and seed yield at the second season. In addition, the results of the third season indicate that the number of seeds/plant correlated significantly and positively with seed yield, and the number of seeds/pod correlated significantly and negatively with seed yield, whereas, number of pods/plant correlated high significantly and positively with the seed yield. The character first node height showed maximum direct effect value in seed yield at the first season and the third season, while number of pods/plant showed maximum direct effect value in seed yield at the second season.